2002
DOI: 10.4148/2378-5977.3167
|View full text |Cite
|
Sign up to set email alerts
|

Milking frequency, estradiol cypionate, and bST alters milk yield and reproductive outcomes in dairy cows (2002)

Abstract: The objective of this study was to determine how milking frequency, estradiol cypionate (ECP) postpartum therapy given at 1 week after calving, and biweekly bovine somatotropin (bST) administration alter lactational and reproductive outcomes in dairy cattle. Holstein cows (n=144) were randomly assigned to eight treatments (18 cows per treatment): 1) twice daily milking frequency (2x), 10-mg injection of ECP at 1 week after calving (ECP), and bST (given biweekly according to label beginning in the ninth week of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a concurrent study to the one reported herein, in which cows in the same herd were diagnosed not pregnant and then assigned to either the Ovsynch or Heatsynch protocols (without CIDR inserts), pregnancy rates did not differ (64/219 or 29.2% vs. 63/229 or 27.5%; Stevenson and Tiffany, unpublished data). In another experiment (Blevins et al, 2002) conducted concurrently with the present report, in which 141 cows were assigned to the Heatsynch protocol for insemination at their first service, pregnancy rates averaged 40% when assessed at 30 to 35 d after TAI.…”
mentioning
confidence: 62%
“…In a concurrent study to the one reported herein, in which cows in the same herd were diagnosed not pregnant and then assigned to either the Ovsynch or Heatsynch protocols (without CIDR inserts), pregnancy rates did not differ (64/219 or 29.2% vs. 63/229 or 27.5%; Stevenson and Tiffany, unpublished data). In another experiment (Blevins et al, 2002) conducted concurrently with the present report, in which 141 cows were assigned to the Heatsynch protocol for insemination at their first service, pregnancy rates averaged 40% when assessed at 30 to 35 d after TAI.…”
mentioning
confidence: 62%